Benang Banten Sebagai Identitas Masyarakat Hindu Di Panti Jompo Tresna Werda Jara Mara Pati - Putu Bratria Dama Dayanu (Pramana: Jurnal Hasil Penelitian, 2023)
The purpose of this article is to get to know, understand, and understand more deeply about Banten Yarn as the identity of the Hindu community at the Tresna Werda Jara Mara Pati Nursing Home. The method used to find out about Banten Yarn as the identity of the Hindu community at the Tresna Werda Jara Mara Pati Nursing Home in this article is to use the literature review method. Banten yarn is categorized as a ceremonial material used by Hindus in religious traditions on the island of Bali. The discussion regarding the use of Banten thread on hands shows that: 1) the use of Banten thread on hands is a must in its use because it is believed to be the identity of the Balinese people, especially people who are Hindus; 2) the banten thread that is placed on the wrist is interpreted as a form of self-protection and self-control for the Hindu community in Bali; 3) the impact that will occur if the Banten Yarn is not interpreted as it should be, namely a shift in essence that begins as material for ceremonies.